The management of moderate pph: an audit from the royal infirmary Edinburgh. (18th April 2012) - Palaniappan, N; Simpson, L; Keag, O; Mary, N
Abstract : Background: Primary post-partum haemorrhage (PPH) is defined as a blood loss of more than 500mls following delivery. Emergency measures are required to be initiated when a blood loss exceeds 1000mls, as healthy patients are usually expected to cope with a blood loss under this level. Moderate PPH (1000-2500mls) that forms a major bulk of all significant PPH is not subjected to routine analysis as major PPH (>2500mls). Aim: The primary aim of the audit was to assess the management of "moderate" PPH. Methods: Retrospective audit for the year 2009. Results: Total deliveries numbered 6678 of which 464 (6.9%) had a PPH exceeding 1000mL. 417 (6.2%) fitted our moderate PPH category (1000-2500mL). 351 (74%) notes were available for analysis. Syntocinon/syntometrine was effectively used in 99.7% of the cases, oxytocin infusion was used in 66%, Ergometrine was used in 23%, and Carboprost was used in 23%. 11% had manual removal of placenta, 1% had an intrauterine balloon insertion. Only 50% of these patients were observed in the HDU postnatally. Conclusion: Strict adherence to the protocol was seen in majority of the cases although a small deviation from the protocol with beneficial effects to the patient was not uncommon. A methodical use of pharmacological agents was observed. However admission to HDU and documentation were areas for improvement. A user-friendly PPH questionnaire has been written and a prospective audit has been suggested to promote accurate documentation. An audit on HDU admissions has been suggested to assess the optimal use of HDU beds.